Effects of Oxidation Agents and Metal Ions on Binding of p53 to Supercoiled DNA - Fojta, M; Brazdova, M; Cernocka, H; Pecinka, P; Brazda, V; Palecek, J; Jagelska, E; Vojtesek, B; Pospisilova, S; Subramaniam, V; Jovin, T M; Palecek, E (Journal of biomolecular structure & dynamics, 2000)
Summary Wild type human full length (f.1.) tumor suppressor p53 protein binds preferentially to super-coiled (sc) DNA in vitro both in the presence and absence of the p53 consensus sequence (p53CON). This binding produces a ladder of retarded bands on the agarose gel. Bands revealed by immunoblotting with antibody DO-1 corresponded to the ethidium stained retarded bands. The intensity and the number of bands of p53-scDNA complex were decreased by physiological concentrations of unchelated zinc ions. Nickel and cobalt ions inhibited binding of p53 to scDNA and to p53CON in linear DNA fragments less efficiently than zinc. Compared to the intrinsic zinc strongly bound to Cys 176, Cys 238, Cys 242 and His 179 in the p53 core domain, binding of additional Zn(2+) to p53 was much weaker as shown by an easy removal of the latter ions by low concentrations of EDTA. Oxidation of the protein with diamide resulted in a decrease of the number of the retarded bands. Under the same conditions, no binding of oxidized p53 to p53CON in a linear DNA fragment was observed. In agreement with the literature oxidation of f.1. p53 with diamide was irreversible and was not reverted by an excess of DTT. We showed that in the presence of 0.1 mM zinc ions, oxidation of p53 became reversible. Other divalent cations tested (cadmium, cobalt, nickel) exhibited no such effect. We suggested that the irreversibility of p53 oxidation was due, at least in part, to the removal of intrinsic zinc from its position in the DNA binding domain (after oxidation of the three cysteines to which the zinc ion is coordinated in the reduced protein) accompanied by a change in the p53 conformation. Binding of C-terminal anti-p53 antibody also protected bacterially expressed protein against irreversible loss of activity due to diamide oxidation. Binding the human p53 core domain (segment 94-312) to scDNA greatly differed from that observed with the full-length p53. The core domain did not posses the ability to bind strongly to many sites in scDNA regardless of the presence or absence of p53CON suggesting involvement of some other domain (probably C-terminal) in binding of the full-length p53 to scDNA. Supershift experiments using antibodies against p53 N- or C-terminus suggested that in oxidized p53, scDNA binding through the C-terminus gained importance.
Keywords: DNA, Superhelical; vazba proteinů; Metals; Tumor Suppressor Protein p53; DNA; lidé; Oxidants; superhelikální DNA; Binding Sites; vazebná místa; kovy; Protein Binding; nádorový supresorový protein p53; oxidancia; Humans